North East India - An overview of political frameworks, economy and connectivity - Pulipaka, Sanjay; Sircar, Saranya; Gorthi, Harisha (2016)
This article gives an overview of North-East as a region in India. It is divided into three segments. The first section gives a brief overview of state formation, autonomous district councils, and conflict in North- East India. The second section deals with economic dimensions such as policy frameworks, development indicators, and natural resources management. The final section maps the recent connectivity projects and calls for greater interaction between North-East India and its eastern neighbours.
Keywords: Economic and social development - India, North East; Economic and social development